Serum PTH reference values established by an automated third-generation assay in vitamin D-replete subjects with normal renal function: consequences of diagnosing primary hyperparathyroidism and the classification of dialysis patients - Souberbielle, Jean-Claude; Massart, Catherine; Brailly-Tabard, Sylvie; Cormier, Catherine; Cavalier, Etienne; Delanaye, Pierre; Chanson, Philippe (European journal of endocrinology, 2016)
ObjectiveTo determine parathyroid hormone (PTH) reference values in French healthy adults, taking into account serum 25-hydroxyvitamin D (25OHD), renal function, age, gender, and BMI.Participants and main biological measurements We studied 898 healthy subjects (432 women) aged 18–89 years with a normal BMI and estimated glomerular filtration rate (eGFR), 81 patients with surgically proven primary hyperparathyroidism (PHPT), and 264 dialysis patients. 25OHD and third-generation PTH assays were implemented on the LIAISON XL platform.Results Median PTH and 25OHD values in the 898 healthy subjects were 18.8 ng/l and 23.6 ng/ml respectively. PTH was lower in subjects with 25OHD ≥30 ng/ml than in those with lower values. Among the 183 subjects with 25OHD ≥30 ng/ml, those aged ≥60 years (n=31) had higher PTH values than younger subjects, independent of 25OHD, BMI, and eGFR (P<0.001). Given the small number of subjects aged ≥60 years, we adopted the 95% CI of PTH values for the entire group of 183 vitamin D-replete subjects (9.4–28.9 ng/l) as our reference values. With 28.9 ng/l as the upper limit of normal (ULN) rather than the manufacturer's ULN of 38.4 ng/l, the percentage of PHPT patients with ‘high’ PTH values rose to 90.1% from 66.6% (P<0.001), and 18.6% of the dialysis patients were classified differently in view of the KDIGO target range (two to nine times the ULN).Conclusion When only subjects with 25OHD ≥30 ng/ml were included in the reference population, the PTH ULN fell by 22.4%, diagnostic sensitivity for PHPT improved, and the classification of dialysis patients was modified.